Can Denmark threaten, lie, and mislead? Influence operations from a legal perspective - Schack, Marc (Politica, 2023)
A state like Denmark, which is committed to the rule of law, is characterized by its democratic foundations, adherence to legal principles such as equality before the law, and a commitment to the protection of fundamental freedoms. This stands in contrast to other types of states where such elements are either absent or subdued. The question is what this contrast means for Denmark’s ability to carry out or counter-influence operations. In this article, Denmark’s ability to handle such operations is considered based on an analysis of key rules that bind the Danish state. Since the topic is, in principle, extensive, the article focuses on three legal issues: the duty of truthfulness for Danish authorities, the international legal principle of sovereignty, and the regulation of the use of force and armed conflict.